Leveraging Artificial Intelligence to Accelerate Patient Diagnostics Efficiency in Rural India - Thombare, Diptii; Mishra, Abhishek; Provodnikova, Dr. Anna (Global journal of Business and Integral Security, 2023)
India has made significant advancement in healthcare and has reduced the gap between urban and rural or rich and poor. The doctor to population ratio is almost near to what is prescribed by World Health Organization. However, there are still some disparities that remain when it comes to access to healthcare and doctors in rural areas. Artificial Intelligence can bridge the gap here. Artificial Intelligence can play a major role by augmenting the capabilities of the doctors in performing efficient and quick diagnostics in rural India. Artificial Intelligence uses rich algorithms, neural networks, deep learning, and advanced analytics to triage critical findings in medical imaging and radiology, diagnose cancer and other life-threatening diseases, predict heart strokes, and many such scenarios. Satellite hospitals and diagnostic centres can be set up in remote villages and towns where there are limited healthcare facilities and using remote sensor devices, patient health data can be collected, Artificial Intelligence can analyse the patient health data, diagnose health issues, and suggest a course of treatment. Artificial Intelligence can greatly reduce the workload of doctors in rural India.